2019
DOI: 10.1038/s41598-018-37935-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurological sequel of chronic kidney disease: From diminished Acetylcholinesterase activity to mitochondrial dysfunctions, oxidative stress and inflammation in mice brain

Abstract: With increasing prevalence, chronic kidney disease (CKD) has become a global health problem. Due to the retention of uremic toxins, electrolytes and water, and the resultant metabolic disturbances, CKD affects several organs, including the nervous system. Thus, CKD patients suffer from several neurological complications, including dementia, cognitive impairment, motor abnormalities, depression, and mood and sleep disturbances. However, the mechanisms underlying the neurological complications are least elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 112 publications
1
42
1
2
Order By: Relevance
“…More recently, in an experimental study with CKD induced by 4 weeks of adenine-rich diet, animals developed depressive-like behavior, locomotor alterations, and cognitive decline. In parallel with these behavioral and cognitive changes, animals also had decreased catalase and increased superoxide dismutase activities, elevated lipid peroxidation, and enhanced NOS-active neurons and dysfunction of mitochondrial complexes in key areas like striatum, substantia nigra, cortex, and hippocampus (Mazumder et al, 2019). Altogether, these experimental studies support the involvement of oxidative stress in neuropsychiatric disorders secondary to CKD.…”
Section: Brain-renal Axis: An Evolving Conceptmentioning
confidence: 99%
“…More recently, in an experimental study with CKD induced by 4 weeks of adenine-rich diet, animals developed depressive-like behavior, locomotor alterations, and cognitive decline. In parallel with these behavioral and cognitive changes, animals also had decreased catalase and increased superoxide dismutase activities, elevated lipid peroxidation, and enhanced NOS-active neurons and dysfunction of mitochondrial complexes in key areas like striatum, substantia nigra, cortex, and hippocampus (Mazumder et al, 2019). Altogether, these experimental studies support the involvement of oxidative stress in neuropsychiatric disorders secondary to CKD.…”
Section: Brain-renal Axis: An Evolving Conceptmentioning
confidence: 99%
“…Cognitive decline is one of the most common neurological symptoms in CKD patients (12-15, 17, 30). Numerous experiments have confirmed deficit in spatial- (23,45), recognition- (21,42,(45)(46)(47), as well as aversive-related memory (46)(47)(48) in CKD animals. On the contrary, there are also some experiments which failed to show memory-impairing effect of CKD (24,49).…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that mild CKD may lead to activation of limbic system, central sympathetic, stress-and pain-related brain areas (31). Some CKD-related neurological complications have been attributed to impaired permeability of the blood-brain barrier (22,32,33), neuroinflammation, and oxidative stress (21)(22)(23). Neurotoxicity induced by numerous substances, such as urea, accumulated in blood during kidney disease (34)(35)(36) might also play a role (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations